Contributions to the analysis of radially compressed variable-angle tow filament-wound composite cylinders: computational and experimental advances - Souza, Gabriel Sales Candido (2025)
This doctoral thesis investigates the mechanical response and failure mechanisms of variableangle tow filament-wound composite (VAT-FWC) cylinders under radial compression. Motivated by the growing interest in curvilinear fiber laminates and the lack of experimental studies on non-planar VAT structures, the work combines experimental testing, finite element modeling, and analytical tools to provide a comprehensive understanding of the structural behavior of these complex systems. Initially, a novel approach is proposed to extract damage evolution laws for composite laminates through quasi-static cyclic tests, aiming to simplify the identification process while maintaining physical reliability. VAT-FWC cylinders are then manufactured using a custom filament winding setup and subjected to radial compression tests with and without stress concentrators. Full-field strain measurements are acquired via three-dimensional digital image correlation, enabling detailed analysis of damage initiation and propagation. Subsequently, a progressive failure analysis is implemented through a finite element framework using experimentally calibrated damage models. The model captures critical aspects such as the damage pathway, damage thresholds, and the influence of local mosaic patterns. Validation is performed by comparing computational predictions with experimental results at both global (forcedisplacement curves) and local levels (strain fields and failure modes). An analytical model is also employed to estimate the crushing tolerance of the cylinders, providing a valuable cross-comparison with experimental and computational data. The results demonstrate that VAT designs can enhance load redistribution and mitigate full-section failure through non-uniform stiffness distributions for cylindrical structures. The proposed modeling strategy proves robust in reproducing failure progression in complex geometries, establishing a foundation for the future design of damage-tolerant composite VAT-configured structures. This research advances the state-of-the-art in modeling and characterization of filament-wound composite cylinders with variable stiffness, with implications for aerospace, automotive, and energy sectors.